EFEITOS FISIOLÓGICOS E METABÓLICOS EM TOMATEIRO POR ESTROBILURINAS E CARBOXAMIDAS - Marek, Janaina (2018)
The objective of this research was to evaluate the physiological and metabolic effects of Conquistador hybrid tomato plants, cultivated in greenhouse and inoculated, with the application of strobilurins and carboxamides. The study was realized in two years (2015 and 2016), in which the effects of the different fungicides on the development of tomato plants, on the photosynthetic efficiency, on the antioxidative system, on the control of the disease and on the activation of defense mechanisms were evaluated the pathogen, as well as in the production and post-harvest of fruits. The experimental design was a randomized block with seven treatments and five replicates, each plot being composed of four plants. The treatments used were: T1 – inoculated control (water + inoculum); T2 – absolute control (water); T3 – boscalide (0.075 g L-1); T4 – boscalide (0.100 g L-1) + kresoxim-methyl (0.050 g L-1); T5 – pyraclostrobin (0.100 g L-1); T6 – fluxapiroxade (0.058 g L-1) + pyraclostrobin (0.116 g L-1) and T7 – methyram (1,100 g L-1) + pyraclostrobin (0.100 g L-1). The effect of treatments on development was evaluated by plant height, leaf area, fresh and dry mass of leaves, stem and root. To verify the photosynthetic efficiency, gas exchange, chlorophyll a fluorescence, pigment content, nitrate reductase enzyme activity and carbohydrate content were evaluated. In order to verify the effects of treatments in the antioxidative system, in the control of the disease and activation of defense mechanisms to the pathogen, the area under the disease progress curve (AUDPC), concentration of superoxide anion and hydrogen peroxide, activity of the enzymes superoxide dismutase, ascorbate peroxidase, glutathione reductase, glutathione S-transferase, glutathione peroxidase, catalase, phenylalanine ammonia-lyase, chitinase, β-1,3-glucanase, peroxidase, polyphenoloxidase and lipoxygenase, in addition to the phenolic compounds content, lipid peroxidation and deposition of lignin. In order to evaluate the effects of the treatments on fruit production and post harvesting, fruit firmness, pH, soluble solids, titratable acidity, ratio solid silts/titratable acidity (SS/AT), ascorbic acid content, pectinametilesterase and polygalacturonase enzyme activity, and mass loss. Based on the results obtained, it can be concluded that the treatments fluxapiroxade plus pyraclostrobin, followed by metiram plus pyraclostrobin stood out from the other treatments, as they presented better plant development and fruit production, due to the higher photosynthetic efficiency, higher enzyme activities of antioxidative defense and activation of defense responses against the attack of the pathogen.